AUTHENTIC MATERIAL ORIENTED TASKS IN ENGLISH TEXTBOOKS - sumadi sumadi; Taniya Taniya (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
this research aims to explore authentic material oriented tasks  in the two selected textbooks for 10th grade of Senior High School in Indonesia. The is qualitative research using the document analysis. The data were collected from two textbooks, i.e., "Bahasa Inggris Kelas X" (Book 1) published by The Ministry of Education and Culture and "Bahasa dan Sastra Inggris Kelas X" (Book 2) published by Yrama Widya. The authentic tasks in the textbooks were analyzed based on skill focus, principles used, and sources used. The result shows that only a few tasks are authentic in both textbooks. Only 5 out of 287 tasks are authentic in Book 1. Book 2 has slightly more authentic tasks. 10 out of 211 tasks are authentic in Book 2. Book 1 focuses on reading skills (71%) whereas Book 2 focuses on writing skills (90%). In terms of the principles used, the result shows that both books use slightly different principles. Book 1 uses the principles of ‘having a real/genuine communicative purpose’ and ‘using real/fact information’ while Book 2 focuses on ‘using a real fact and information’. Moreover, the sources used in authentic material-oriented tasks particularly found in Book 1 are printed media and internet devices while in Book 2, internet devices are mostly used as the source. In conclusion, both English textbooks provide less authentic material-oriented tasks than pedagogical tasks.